2012
DOI: 10.1016/j.cmet.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonists Induce a White-to-Brown Fat Conversion through Stabilization of PRDM16 Protein

Abstract: Brown adipose tissue dissipates energy through heat and functions as a defense against cold and obesity. PPAR ligands have been shown to induce the browning of white adipocytes; however, the underlying mechanisms remain unclear. Here we show that PPAR ligands require full agonism to induce a brown fat gene program preferentially in subcutaneous white adipose. These effects require expression of PRDM16, a factor that controls the development of classical brown fat. Depletion of PRDM16 blunts the effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
665
2
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(713 citation statements)
references
References 47 publications
29
665
2
17
Order By: Relevance
“…For example, depletion of PRDM16 leads to a significant loss in the cold and TZD-induced browning of white adipocytes. 31,32 We have previously shown that rosiglitazone robustly extends the half-life of PRDM16 protein from 5.9 to 17.5 h. 32 The TZD-induced stabilization of PRDM16 protein is mediated through the ubiquitin-proteasome pathway, although specific E3 ubiquitin ligase(s) for PRDM16 has not been identified (Figure 1b). This finding explains well the slow kinetics of WAT browning in response to rosiglitazone treatment; TZD-mediated WAT browning requires at least 3 days or longer in cultured cells, whereas most of the direct target genes of PPARγ are activated by rosiglitazone within several hours.…”
Section: Regulation Of Prdm16 Transcriptional Activities In Wat Browningmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, depletion of PRDM16 leads to a significant loss in the cold and TZD-induced browning of white adipocytes. 31,32 We have previously shown that rosiglitazone robustly extends the half-life of PRDM16 protein from 5.9 to 17.5 h. 32 The TZD-induced stabilization of PRDM16 protein is mediated through the ubiquitin-proteasome pathway, although specific E3 ubiquitin ligase(s) for PRDM16 has not been identified (Figure 1b). This finding explains well the slow kinetics of WAT browning in response to rosiglitazone treatment; TZD-mediated WAT browning requires at least 3 days or longer in cultured cells, whereas most of the direct target genes of PPARγ are activated by rosiglitazone within several hours.…”
Section: Regulation Of Prdm16 Transcriptional Activities In Wat Browningmentioning
confidence: 99%
“…Theoretically, 3-day-treatment with rosiglitazone results in the accumulation of PRDM16 protein by~250-fold, in accordance well with the slow kinetics of browning effects by PPARγ agonists. 32 More recently, the Accili's group also proposed an additional mechanism in which Sirt1-dependent deacetylation of PPARγ enhances the interaction between PRDM16 and PPARγ. 33 These results imply a possibility that stabilization of PRDM16 protein may be a plausible strategy to induce WAT browning without directly agonizing the PPARγ transcriptional activity.…”
Section: Regulation Of Prdm16 Transcriptional Activities In Wat Browningmentioning
confidence: 99%
“…After analyzing various mouse WAT depots, we noted that Prdm16 is highly expressed in the depots that are most prone to beiging, especially the inguinal WAT 16 . Importantly, reduction of Prdm16 expression blocks the induction of a thermogenic program in cultured subcutaneous adipocytes and decreases the recruitment of beige adipocytes in WAT in response to β-adrenergic or Ppar-γ agonists 16,43 . Conversely, transgenic expression of Prdm16 in adipose tissues of mice stimulates beige adipocyte development to counteract high fat diet-induced weight gain and improve glucose tolerance 16 .…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%
“…Additionally, thiazolidinediones (TZDs), which agonize Ppar-γ, induce thermogenic gene expression in fat cells through effects on Prdm16 (refs. 43,47). Interestingly, the muscle-enriched microRNA miR-133 directly targets and reduces the amounts of Prdm16 to block both brown and beige adipose development [46][47][48] .…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%
“…However, analyses of cells already committed to brown adipocyte differentiation have shown that PPARγ activation specifically enhances the expression of UCP1 and other specific markers of brown adipocyte phenotype. 30 Thiazolidinedione treatment in vivo recruits BAT depots and promotes the browning of WAT, but there are indications that parallel noradrenergic activation is required for thiazolidinediones to produce effective thermogenic induction. 31 In contrast to PPARγ, which is expressed in and regulates adipogenesis in both white and brown adipocytes, PPARα is preferentially expressed in BAT, 32 and genetic data point to PPARα as an essential component of the BAT-specific phenotype.…”
Section: Hormones Vitamins and Metabolites That Act Through Nuclearmentioning
confidence: 99%